2018
DOI: 10.1177/0956797618776942
|View full text |Cite
|
Sign up to set email alerts
|

Early Gender Differences in Core Values Predict Anticipated Family Versus Career Orientation

Abstract: Communion and agency are often described as core human values. In adults, these values predict gendered role preferences. Yet little work has examined the extent to which young boys and girls explicitly endorse communal and agentic values and whether early gender differences in values predict boys' and girls' different role expectations. In a sample of 411 children between the ages of 6 and 14 years, we found consistent gender differences in endorsement of communal and agentic values. Across this age range, bo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
37
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
10

Relationship

3
7

Authors

Journals

citations
Cited by 36 publications
(41 citation statements)
references
References 18 publications
4
37
0
Order By: Relevance
“…For example, a cross-cultural study found that men (vs. women) preferred competitive situations in nearly all of the 36 countries examined (mean d = 0.36; range = 0.63 [U.S.] to 0.13 [Slovak Republic]) (Bönte, 2015; see also Gneezy & Rustichini, 2004). Some research reveals that by age 6, boys value "being the best" more than girls do (Block, Gonzalez, Schmader, & Baron, 2018). A study in India indicated that a gender gap in competitiveness WOMEN PSYCHOLOGICAL SCIENCE -49 emerged around middle childhood to early adolescence, at least in patrilineal subcultures (d = -1.1; Andersen, Ertac, Gneezy, List, & Maximiano, 2013); no difference was observed in matrilineal subcultures (d = 0.18).…”
Section: Issue #9: Agency Self-esteem and Self-promotionmentioning
confidence: 99%
“…For example, a cross-cultural study found that men (vs. women) preferred competitive situations in nearly all of the 36 countries examined (mean d = 0.36; range = 0.63 [U.S.] to 0.13 [Slovak Republic]) (Bönte, 2015; see also Gneezy & Rustichini, 2004). Some research reveals that by age 6, boys value "being the best" more than girls do (Block, Gonzalez, Schmader, & Baron, 2018). A study in India indicated that a gender gap in competitiveness WOMEN PSYCHOLOGICAL SCIENCE -49 emerged around middle childhood to early adolescence, at least in patrilineal subcultures (d = -1.1; Andersen, Ertac, Gneezy, List, & Maximiano, 2013); no difference was observed in matrilineal subcultures (d = 0.18).…”
Section: Issue #9: Agency Self-esteem and Self-promotionmentioning
confidence: 99%
“…Recent research and theorizing argue that young children's experiences are deeply influenced by stereotypes of girls and women as being communal and other-oriented, and boys and men as being agentic and self-focused (see Croft et al, 2015 for a detailed review of this process). This heavy gender stereotype influence on childhood development can lead boys and girls to adopt a self-view that is in line with such beliefs to the extent that they even display implicit or automatic levels of self-stereotyping (Baron et al, 2014;Block, Gonzalez, et al, 2018). Over the span of a lifetime of conceptualizing oneself through the lens of a particular gender identity category (i.e., primarily male or female), a person would also come to perceive their own skills and ability levels to be consistent with those of their gender (Baron et al, 2014;.…”
Section: Proximal Factors That Contribute To Gripmentioning
confidence: 99%
“…As noted, one of the main drivers of male engagement in communal roles are gender norms socializing men to be less communal than women (Martin & Ruble, ; Wood & Eagly, ). Boys’ and men's relatively lower communal values have been shown to explain lower family aspirations in young boys, as well as lower interest in HEED careers in men (Block, Croft, & Schmader, ; Block, Gonzalez, Schmader, & Baron, ). In order to reduce barriers to men's communal engagement then, the most basic and necessary level is to start early, with less gender‐rigid socialization of boys.…”
Section: Tackling Barriers To Men's Communal Engagement At the Societmentioning
confidence: 99%